Mediating Factors in Martial Arts and Combat Sports: An Analysis of the Type of Martial Art, Characteristics, and Social Background of Young Participants. Issue 1 (February 2014) - Vertonghen, Jikkemien; Theeboom, Marc; Pieter, Willy
To date, most studies regarding the social-psychological effects of martial arts and combat sports (MA&CS) on young people focus on measuring effects without considering mediating factors. The aim of the present study was to analyze three mediating factors that might be influential when examining outcomes of MA&CS for youth (i.e., the type of MA&CS, participants' characteristics, and social background). Young MA&CS participants ( N = 477, M age = 14.0 yr., SD = 2.13) practicing judo, aikido, kick-/Thai boxing or karate, as well as their parents ( N = 307), were assessed in terms of their goal orientations, aggressiveness, psychosocial behavior, and social background. It was concluded that differences exist in the characteristics and social background of participants depending on the type of MA&CS being practiced. The fact that differences in these mediating factors can be identified indicates that in future research these and possible other mediating factors should be considered when trying to determine social-psychological outcomes of MA&CS.